Salt tolerance variability among stress‐selected Panicum coloratum cv. Klein plants - Pittaro, Gabriela; Caceres, Leandro; Bruno, Cecilia Inés; Tomas, Maria Andrea; Bustos, Dolores Angela; Monteoliva, Mariela Ines; Ortega, Leandro Ismael; Taleisnik, Edith (Wiley; British Grassland Society; European Grassland Federation, 2019)
This work assessed intracultivar variability for salt tolerance within Panicum coloratum cv. Klein, explored some physiological parameters potentially associated with it and evaluated the contribution of cell division and expansion to the decreased leaf length observed under salinity. Individual plants that had survived severe stress environments in an established pasture were collected and clonal families were obtained by vegetative propagation. These were evaluated in a greenhouse, in pots with an inert substrate irrigated with nutrient solution containing 0, 200 or 400 mm NaCl. Salt tolerance was assessed from growth variables expressed as a percentage of non‐salinized controls. Changes induced by salinity in carbon fixation, soluble sugars and compatible solutes were also measured. The selected plants showed 33% higher salt tolerance than plants from the same cultivar obtained from seeds, and variability for salt tolerance was detected within the group, suggesting these plants could be valuable germplasm for breeding programmes for saline areas. All selected plants accumulated low leaf blade Na concentrations (< 0·1 mm g−1 dry weight on average), and K concentrations tended to remain high under salinity. A kinematic analysis indicated a reduction in the number of cells in the division‐only zone was the main cause of shorter leaves under stress. Although plants showed some differences in all these traits, they were not related to salt‐tolerance variability within this group of stress‐tolerant plants.